miR-146a-5p and miR-193a-5p Synergistically Inhibited the Proliferation of Human Colorectal Cancer Cells (HT-29 cell line) through ERK Signaling Pathway - Saeed Noorolyai; Elham Baghbani; Dariush Shanehbandi; Vahid Khaze Shahgoli; Amir Baghbanzadeh Kojabad; Behzad Mansoori; Khalil Hajiasgharzadeh; Ahad Mokhtarzadeh; Behzad Baradaran (Tabriz University of Medical Sciences, 2021)
Purpose: The expression of miR-146a-5p and miR-193a-5p in colorectal cancer (CRC) is associated with cancer development, metastasis, and reduced survival rate of the tumor-suffered subjects. This examination aimed to assess the impact of these microRNAs (miRNAs) in CRC and their mechanisms in the proliferation and migration of cancer cells. Methods: miR-146a-5p and -193a-5p were transfected into the HT-29 cell line and assessed their impact on metastasis-related genes. The synergistic effects of these miRNAs on migration were evaluated by wound healing approach. To assess the influence of these miRNAs on the proliferation of and apoptosis of cells, the MTT test, annexin V staining test, and DAPI staining test were done. Then, the protein expression of extracellular-signal-regulated kinase (ERK) and phosphorylated ERK (p-ERK) were investigated. Results: miR-146a-5p and-193a-5p could inhibit the CRC cells proliferation, and could synergistically induce apoptosis in CRC cells, and also repressed cell migration, and could reduce p-ERK expression. Conclusion: miR-146a-5p and-193a-5p have an important role in cell viability and proliferation via ERK signaling pathway. Thus, the simultaneous use of these miRNAs may be suggested as a probable therapeutic strategy in this cancer therapy.